Modulating TNFα activity allows transgenic IL15-Expressing CLL-1 CAR T cells to safely eliminate acute myeloid leukemia. Issue 2 (16th September 2020) - Ataca Atilla, Pinar; McKenna, Mary K; Tashiro, Haruko; Srinivasan, Madhuwanti; Mo, Feiyan; Watanabe, Norihiro; Simons, Brian Wesley; McLean Stevens, Alexandra; Redell, Michele S; Heslop, Helen E; Mamonkin, Maksim; Brenner, Malcolm K; et al.
Abstract : Background: C-type lectin-like molecule 1 (CLL-1) is highly expressed in acute myeloid leukemia (AML) but is absent in primitive hematopoietic progenitors, making it an attractive target for a chimeric antigen receptor (CAR) T-cell therapy. Here, we optimized our CLL-1 CAR for anti-leukemic activity in mouse xenograft models of aggressive AML. Methods: First, we optimized the CLL-1 CAR using different spacer, transmembrane and costimulatory sequences. We used a second retroviral vector to coexpress transgenic IL15. We measured the effects of each construct on T cell phenotype and sequential (recursive) co culture assays with tumor cell targets to determine the durability of the anti tumor activity by flow cytometry. We administered CAR T cells to mice engrafted with patient derived xenografts (PDX) and AML cell line and determined anti tumor activity by bioluminescence imaging and weekly bleeding, measured serum cytokines by multiplex analysis. After euthanasia, we examined formalin-fixed/paraffin embedded sections. Unpaired two-tailed Student's t-tests were used and values of p<0.05 were considered significant. Survival was calculated using Mantel-Cox log-rank test. Results: In vitro, CLL-1 CAR T cells with interleukin-15 (IL15) were less terminally differentiated (p<0.0001) and had superior expansion compared with CD28z-CD8 CAR T cells without IL15 (p<0.001). In both AML PDX and AML cell line animal models, CLL-1 CAR T coexpressing transgenic IL15 initially expanded better than CD28z-CD8 CAR T without IL15 (p<0.0001), but produced severe acute toxicity associated with high level production of human tumor necrosis factor α (TNFα), IL15 and IL2. Histopathology showed marked inflammatory changes with tissue damage in lung and liver. This acute toxicity could be managed by two strategies, individually or in combination. The excessive TNF alpha secretion could be blocked with anti-TNF alpha antibody, while excessive T cell expansion could be arrested by activation of an inducible caspase nine safety switch by administration of dimerizing drug. Both strategies successfully prolonged tumor-free survival. Conclusion: Combinatorial treatment with a TNFα blocking antibody and subsequent activation of the caspase-9 control switch increased the expansion, survival and antileukemic potency of CLL-1 CAR T-cells expressing transgenic IL15 while avoiding the toxicities associated with excessive cytokine production and long-term accumulation of activated T-cells.